PENGARUH STRUKTUR GOOD CORPORATE GOVERNANCE DAN ENVIRONMENTAL PERFORMANCE TERHADAP CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE - Karina Avelya Putri; Eni Wuryani (STIE Mahardhika, 2026)
This study examines the factors that influence Corporate Social Responsibility (CSR) disclosure in the energy sector, particularly in companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2024. This study focuses on the interaction between corporate governance structure and environmental performance on CSR disclosure. The governance structure includes the size of the board of directors, the proportion of independent commissioners, the independence of the audit committee, and managerial ownership. This study uses a quantitative method by processing 72 observations obtained through purposive sampling using multiple linear regression in SPSS 26. The findings show that a larger board of directors and better environmental performance encourage higher CSR disclosure. On the other hand, audit committee independence has a negative impact on CSR disclosure, while the proportion of independent commissioners and managerial ownership have no significant effect on CSR disclosure.